OMNICHANNEL DIGITAL MARKETING STRATEGIES IN FMCG DISTRIBUTION: ENHANCING SUSTAINABILITY THROUGH AI INTEGRATION (Marketing Journal, 2025)
This thesis explores how AI-integrated omnichannel digital marketing strategies in FMCG distribution contribute to sustainability. It analyzes how AI enhances personalization, predictive analytics, and automation across digital platforms to reduce waste and resource use. The study emphasizes the alignment of marketing efficiency with ecological responsibility and highlights opportunities for Central Asia, particularly Uzbekistan, in adopting these innovations. Policy, infrastructure, and digital literacy are identified as key enablers of sustainable transformation in FMCG marketing.